If Nigeria’s Economic Performance From 1960–2020 Resembled China’s and South Korea’s: Exploring the Counterfactual and Subjunctive in Economics - Sohn, Ira (Journal of Applied Business and Economics, 2022)
This paper extends earlier work on Nigeria’s failure to improve living standards for its population when compared with China and South Korea since 1960. The paper employs the use of counterfactuals (‘‘alternate histories and contingent futures”) -- what might have happened had a particular historical event not occurred or occurred differently -- that has long been the domain of historians, not economists. First, I present the main reasons for Nigeria’s poor performance over the last 60 years. Then I consider the “fantasy world of the counterfactual”: What living standards would Nigeria have today if Chinese or South Korean demographic and economic growth rates were applied over this 60 year interval? The value of this “invented scenario” lies in “assigning a cost” to decades of failures in governance and economic management.